Deficits in Working Memory and Theory of Mind May Underlie Difficulties in Social Perception of Children with ADHD - Samane Imanipour; Mahmood Sheikh; Monir Shayestefar; Tourandokht Baloochnejad (Neurology Research International)
Children with attention deficit hyperactivity disorder (ADHD) are prone to peer rejection and disliking due to difficulties in social perception and interaction. To address social perception impairments in ADHD, we examined children with ADHD in a noisy biological motion (BM) direction discrimination paradigm in association with sociocognitive factors including emotion regulation, theory of mind (TOM), and working memory compared to healthy controls. Our results showed that children with ADHD were poorer in discriminating BM direction in noisy environments (F (1, 36) = 4.655, p=0.038). Moreover, a significant correlation was found between working memory and TOM with BM discrimination in an ADHD group (r = 0.442, p=0.01, and r = 0.403, p=0.05, respectively). Our findings could suggest that social perception in noisy scenarios may be affected by memory and social cognitive abilities of children with ADHD.